UPENA organises writing workshop - Wee, Chong Hui (Universiti Teknologi MARA, Sarawak, 2007)
A workshop on writing reference books, organised by the University Publication Centre (UPENA), Universiti Teknologi MARA (UiTM) was held at UiTM Sarawak, Kota Samarahan on 16 - 17 April 2007. The hands-on workshop included evaluation of the participants' draft manuscripts, followed by guidelines for improvements.